Integrated health system intervention aimed at reducing type 2 diabetes risk in women after gestational diabetes in South Africa (IINDIAGO): a randomised controlled trial protocol - Shane A Norris; Carl Lombard; Jean Claude Mutabazi; Katherine Murphy; Naomi Levitt; Christina Zarowsky; Tawanda Chivese; Lara R Fairall; Estelle Lambert; Lisa Jayne Ware; Mushi Matjila; Janetta Harbron; et al. (BMJ Open, 2024)
Introduction South Africa has a high prevalence of gestational diabetes mellitus (GDM; 15%) and many of these women (48%) progress to type 2 diabetes mellitus (T2DM) within 5 years post partum. A significant proportion (47%) of the women are not aware of their diabetes status after the index pregnancy, which may be in part to low postnatal diabetes screening rates. Therefore, we aim to evaluate a intervention that reduces the subsequent risk of developing T2DM among women with recent GDM. Our objectives are fourfold: (1) compare the completion of the nationally recommended 6-week postpartum oral glucose tolerance test (OGTT) between intervention and control groups; (2) compare the diabetes risk reduction between control and intervention groups at 12 months’ post partum; (3) assess the process of implementation; and (4) assess the cost-effectiveness of the proposed intervention package.Methods and analyses Convergent parallel mixed-methods study with the main component being a pragmatic, 2-arm individually randomised controlled trial, which will be carried out at five major referral centres and up to 26 well-baby clinics in the Western Cape and Gauteng provinces of South Africa. Participants (n=370) with GDM (with no prior history of either type 1 or type 2 diabetes) will be recruited into the study at 24–36 weeks’ gestational age, at which stage first data collection will take place. Subsequent data collection will take place at 6–8 weeks after delivery and again at 12 months. The primary outcome for the trial is twofold: first, the completion of the recommended 2-hour OGTT at the well-baby clinics 6–8 weeks post partum, and second, a composite diabetes risk reduction indicator at 12 months. Process evaluation will assess fidelity, acceptability, and dose of the intervention.Ethics and dissemination Ethics approval has been granted from University of Cape Town (829/2016), University of the Witwatersrand, Johannesburg (M170228), University of Stellenbosch (N17/04/032) and the University of Montreal (2019-794). The results of the trial will be disseminated through publication in peer-reviewed journals and presentations to key South African Government stakeholders and health service providers.Protocol version 1 December 2022 (version #2). Any protocol amendments will be communicated to investigators, Human Ethics Research Committees, trial participants, and trial registries.Trial registration number PAN African Clinical Trials Registry (https://pactr.samrc.ac.za) on 11 June 2018 (identifier PACTR201805003336174).